Combining central pattern generators with the electromagnetism-like algorithm for head motion stabilization during quadruped robot locomotion - Santos, Cristina (2009)
Visually-guided locomotion is important for autonomous robotics. However, there are several difficulties, for instance, the head shaking that results from the robot locomotion itself that constraints stable image acquisition and the possibility to rely on that information to act accordingly. In this article, we propose a controller architecture that is able to generate locomotion for a quadruped robot and to generate head motion able to minimize the head motion induced by locomotion itself. The movement controllers are biologically inspired in the concept of Central Pattern Generators (CPGs). CPGs are modelled based on nonlinear dynamical systems, coupled Hopf oscillators. This approach allows to explicitly specify parameters such as amplitude, offset and frequency of movement and to smoothly modulate the generated oscillations according to changes in these parameters. We take advantage of this particularity and propose a combined approach to generate head movement stabilization on a quadruped robot, using CPGs and a global optimization algorithm. The best set of parameters that generates the head movement are computed by the electromagnetism-like algorithm in order to reduce the head shaking caused by locomotion. Experimental results on a simulated AIBO robot demonstrate that the proposed approach generates head movement that does not eliminate but reduces the one induced by locomotion.